Research and design of TiN/TiAlN coated integral cemented carbide reamers under high cutting-speed and high feed-rate machining conditions - ChaoKuan Zhu; Ju Huang; Yong Zhang (Scientific Reports)
Abstract The development of high-performance reamers made of Cemented carbide and coating materials is an important direction in mechanical finishing. Due to the complex structure of reamers, it is difficult to manufacture reamers with good performance in practice. This paper takes the high cutting- speed and high feed-rate mechanical finishing of 45 steel as the experimental condition and the production site machining as the background to scientifically investigate the factors affecting the performance of the TiN/TiAlN coated Integral Cemented carbide reamer. Firstly, the TiN/TiAlN coated cemented carbide reamer was designed and manufactured. During the experimental processing, shrinkage hole over-tolerance problems occurred rapidly. By analyzing the cutting characteristics of the reamer, the mechanical model of the cutting edge of the reamer was established, and the principle of chipping was analyzed. The results were consistent with the magnified fracture morphology of the cutting edge. In response to the accelerated wear caused by poor cooling and lubrication, an internal cooling reamer structure was adopted, and the fluid mechanics model of the Integral reamer was constructed. The important structural parameters were determined, and the importance of adequate cooling and lubrication was clarified. By clarifying the factors affecting the processing performance, the machining capacity of this type of reamer was maximized.